Preeclampsia is associated with increased ambulatory arterial stiffness index in type 1 diabetes mellitus. (September 2017) - Al-Far, Hanine F.M.; Tjessem, Ingvild H.; Fuglsang, Jens; Lauszus, Finn F.
Abstract: Introduction: Treatment of mild to moderate hypertension might not benefit maternal or fetal outcome. This pessimistic point of view may have come about by using non-validated methods for measuring blood pressure in pregnancy combined with inadequate methodology for diagnosis, treatment, and monitoring effects. Aim: To determine the association between AASI in women with type 1 diabetes mellitus (T1DM) and preeclampsia, and to assess the ability of AASI to diagnose preeclampsia. Material and methods: Repeated 24-h ambulatory blood pressure recordings were performed three times during pregnancy and once three months postpartum in 151 women with T1DM and 50 control women without diabetes. Circadian rhythm was evaluated as the night day ratio, night blood pressure divided by day blood pressure. Results: Of the T1DM women, 33 developed preeclampsia, which was associated with AASI in the 3rd trimester (p < 0.05). The best predictor of preeclampsia in T1DM was an AASI of 0.35. The diurnal blood pressure was significantly higher in all trimesters in women who later had preeclampsia. A flattened circadian rhythm was present in T1DM women with preeclampsia compared to women without preeclampsia (night-day ratio: systole 2nd trimester: 0.94 ± 0.07 vs. 0.91 ± 0.05, women with and without preeclampsia, respectively, p = 0.015; diastole 2nd trimester: 0.89 ± 0.07 vs. 0.85 ± 0.07, p = 0.003). AASI was higher during pregnancy compared to postpartum in women with T1DM (0.31 ± 0.16, 0.31 ± 0.16 and 0.33 ± 0.18 vs. 0.25 ± 0.17; 1st, 2nd and 3rd trimester vs. postpartum). Conclusion: Women with T1DM and preeclampsia demonstrate increased arterial stiffness and had early manifestations in the non-dipping of blood pressure.